ANALISIS KINERJA RUKUN TETANGGA (RT) DIKELURAHAN JAYAMUKTI KOTA DUMAI - Isnaini, Isnaini (UIR PRESS, 2017)
: Jaya Mukti is one of the sub-districts in Dumai Timur District East Dumai Urban Village Jaya Mukti is one of urban villages located in the middle of Dumai City with the highest population density among urban villages in Dumai City. To realize JayaMukti Village Mission, Kelurahan is assisted by the performance of the existing Chairman of the RT, and coincides with the respective term of each Chairman of the RT ended in March 2017 then the researcher made a research on how the Head of RT in JayaMukti Kota Dumai by Payaman J. Simanjuntak